Performance Comparison of the Combination of Smarter-Fuzzy and Smarter-Fuzzy-Topsis Methods on the accuracy of the PPA Scholarship Acceptance Decision Support System - I Komang Tri Edi Wardana; I Made Gede Sunarya; I Gede Aris Gunadi (Information Technology and Science (ITScience), 2024)
The PPA Scholarship is a scholarship intended for students who excel, are active in campus activities, and are economically disadvantaged in accordance with predetermined conditions. Currently, STAHN MPU Kuturan Singaraja in calculations often takes a long time, causing delays from the predetermined schedule and less accurate results. Based on this, it is necessary to develop a Decision Support System that can provide recommendations for prospective PPA scholarship recipients. There are 6 criteria being used, including: GPA, semester, credits, charter/certificate, assignment letter, and parent's income. In this study, comparing the performance of the combination of the Smarter-Fuzzy and Smarter-Fuzzy-Topsis methods through testing using the confusion matrix method. Smarter method is used to be able to give weighting criteria with ROC technique. The Fuzzy method is used to convert the criteria values ??for each alternative from 0 to 1. The Topsis method is used to rank. The ranking results of the combination Smarter-Fuzzy method show an accuracy rate of 86.6%, and the combination of the Smarter-Fuzzy-Topsis method of 75.5%.